Molecular Identification and Phylogenetic Analysis of Salmonella‎ species ‎Isolated from Diarrheal Children and Dogs in Baghdad Governorate, ‎Iraq‎ - Abdhalla, Fudhaa; M Al-Gburi, Nagham (The Iraqi Journal of Veterinary Medicine, 2023)
This work aimed to use conventional PCR to identify Salmonella‎ spp. that ‎were isolated from diarrheal children and healthy and diarrheic dogs based on four ‎virulence genes, hilA, stn, spvR‎, and marT. Sixteen Salmonella‎ isolates including: 9 ‎isolated from children’s diarrhea from three species (S. Typhimurium, S. Enteritidis, S. ‎Typhi) and seven isolated from dogs including (S. Typhimurium, S. Enteritidis, S. ‎Muenchen), were identified primarily by several methods. The PCR products of the 16S ‎rRNA gene were sequenced and examined using BLAST analysis to find differences and ‎similarities between these Iraqi isolates and already-known global strains in order to ‎construct the phylogenetic tree of S. Muenchen which was detected for the first time in ‎dogs in Iraq. The results of the study revealed that all isolates of Salmonella‎ obtained ‎from children possess the hilA and stn genes. The marT gene was detected in 88% of the ‎Salmonella‎ serovars, and the spvR‎ gene was carried in 55% of the isolates. Among dog ‎Salmonella‎ isolates, the hilA gene was detected at 100%, the stn gene was at 85.7%, the ‎marT gene was present at 71.4%, while the spvR‎ gene was found at 57.1%. The result of ‎DNA sequencing and phylogenetic tree indicated that the local Iraqi S. Muenchen was ‎extremely close to the national strain and share the same ‎16S rRNA gene sequence, the ‎isolate was registered at NCBI and became a global reference with the accession number OQ999043.1. In conclusion, the presence of these important virulence genes among ‎Salmonella‎ serovars isolated from children and dogs alerted on the potential risk of ‎contamination of the environment and may lead to a community health crisis‎.